The Relationship Between Health Workers' Knowledge And Flood Emergency Response Preparedness - Fatimah Fatimah (Journal of Public Health Indonesian, 2024)
Data from the National Disaster Management Agency (BNPB) reveals that the most common type of disaster is flooding. Based on the 2010-2030 Regional Spatial Plan (RT/RW) document of Padang City, as stipulated in Perda No. 03 of 2019, Article 58 B, there are 10 sub-districts in Padang City that are classified as flood-prone. These sub-districts include Koto Tangah, Kuranji, Pauh, West Padang, East Padang, South Padang, Lubuk Begalung, Nanggalo, Lubuk Kilangan, and Bungus Teluk Kabung. In this context, the preparedness of health workers in facing disasters is very important. This study aimed to assess the relationship between the level of knowledge of health workers and their preparedness in facing floods at Puskesmas Pauh, Padang City. The study was conducted in March 2024 involving 74 respondents as samples. Data were analyzed using the Chi-Square test with a 95% confidence level. Based on the characteristics of the respondents, the majority were between 37 to 47 years old (42 people or 56.8%), had a DIII education (47 people or 63.5%), were female (67 people or 90.5%), and worked as midwifery health workers (38 people or 51.4%). Most of the respondents had good knowledge related to flood disaster preparedness (52.7%) and had a mature emergency response plan (89.2%). The results of this study indicate a significant relationship between the level of knowledge of health workers and flood emergency response preparedness at Puskesmas Pauh, Padang City, with a p-value of 0.006.